Daily travel behavior and emotional well-being: Effects of trip mode, duration, purpose, and companionship. (December 2018) - Zhu, Jing; Fan, Yingling
Abstract: Positive emotions have long-lasting benefits for human development. Understanding the connections between daily travel behavior and emotional well-being will not only help transportation practitioners identify concrete strategies to improve user experiences of transportation services, but also help health practitioners to identify innovative solutions for improving public health. Prior research on the subject had focused on limited travel behavior dimensions such as travel mode and/or travel duration. Other dimensions such as travel purpose and travel companionship have received limited attention. Using data from the 2012–2013 American Time Use Survey, this paper applied the generalized ordered logistic regression approach and examined how the mode, duration, purpose, and companionship characteristics of a trip shape six different emotions during the trip, including happy, meaningful, tired, stressful, sad, and pain. After controlling for personal demographics, health conditions, and residential locations, we find that biking is the happiest mode; public transit is the least happy and least meaningful; and utilitarian walking for transportation is associated with all four negative emotions. Trip duration has a negative association with happiness and a positive association with stress. Travel for discretionary purposes such as leisure, exercise, and community activities is generally associated with higher levels of positive emotions and lower levels of negative emotions than travel for work or household maintenance. Trips with eating and drinking purposes appear to be the happiest and trips with the purpose of spiritual and/or volunteering activities appear to be the most meaningful. Travel with family especially children or travel with friends is happier and more meaningful than travel alone. Transportation planners in the U.S. are recommended to promote biking behavior, improve transit user experiences, and implement spatial planning strategies for creating a built environment conducive to shorter trips, more discretionary trips, and more joint trips with family and friends.